2017
DOI: 10.1080/15476286.2016.1272747
|View full text |Cite
|
Sign up to set email alerts
|

Why so narrow: Distribution of anti-sense regulated, type I toxin-antitoxin systems compared with type II and type III systems

Abstract: Toxin-antitoxin (TA) systems are gene modules that appear to be horizontally mobile across a wide range of prokaryotes. It has been proposed that type I TA systems, with an antisense RNA-antitoxin, are less mobile than other TAs that rely on direct toxin-antitoxin binding but no direct comparisons have been made. We searched for type I, II and III toxin families using iterative searches with profile hidden Markov models across phyla and replicons. The distribution of type I toxin families were comparatively na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 51 publications
(49 reference statements)
0
20
0
1
Order By: Relevance
“…This review will focus on type II systems. These elements are not only found in plasmids but also in other types of mobile genetic elements (such as phages and ICEs) as well as in chromosomes (see e.g., Anantharaman and Aravind, 2003;Pandey and Gerdes, 2005;Guglielmini and Van Melderen, 2011;Leplae et al, 2011;Ramisetty et al, 2016;Coray et al, 2017). While the roles of TAs, when located in mobile genetic elements, are reminiscent to that on plasmids, i.e., maintenance (Szekeres et al, 2007;Wozniak and Waldor, 2009;Huguet et al, 2016), the roles of chromosomally-encoded systems remains a largely debated topic in the field.…”
Section: Introductionmentioning
confidence: 99%
“…This review will focus on type II systems. These elements are not only found in plasmids but also in other types of mobile genetic elements (such as phages and ICEs) as well as in chromosomes (see e.g., Anantharaman and Aravind, 2003;Pandey and Gerdes, 2005;Guglielmini and Van Melderen, 2011;Leplae et al, 2011;Ramisetty et al, 2016;Coray et al, 2017). While the roles of TAs, when located in mobile genetic elements, are reminiscent to that on plasmids, i.e., maintenance (Szekeres et al, 2007;Wozniak and Waldor, 2009;Huguet et al, 2016), the roles of chromosomally-encoded systems remains a largely debated topic in the field.…”
Section: Introductionmentioning
confidence: 99%
“…For other TA types, both the toxin and the antitoxin are proteins. In most studied type II TA systems, the proteinaceous antitoxin forms a complex with its cognate toxin leading to toxin inactivation 14 . Major functions of TA modules include plasmid maintenance, abortive phage infection and persister cell formation 15, 16, 17, 18, 19, 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Toxin–antitoxin (TA) proteins play a crucial role in generating persisters in several bacterial species( 2022 ). These TA systems, known to modulate growth under various growth and stress conditions, are found in wide range of bacterial and archaeal chromosomes and plasmids ( 2325 ). Research conducted during the past decade has clearly demonstrated that TA loci act as effectors of dormancy and persistence in several bacterial species ( 20, 21 ).…”
Section: Introductionmentioning
confidence: 99%